Faktor–faktor yang mempengaruhi pendapatan usaha pedagang ikan di pasar tradisional Kota Jambi - Yudha Titho Syahputra; Parmadi, Parmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2017)
This study aims to analyze: 1) the social and economic characteristics of fish traders in traditional markets in Jambi City; 2) factors that influence the income of fish traders in traditional markets in Jambi City. The data used is sourced from surveys on fish traders in the traditional market of Jambi City. Data were analyzed descriptively and used multiple regression models. The results of the study found: 1) The average age of fish traders in the traditional market of Jambi City was 42.97 years, generally men with dominant education were graduating from high school. All traders are married with an average dependency of 2.51 people; 2) The average initial capital of fish traders is Rp. 2.9 million, with a monthly working capital of Rp. 2.5 million and an average income of Rp. 4.6 million per month. Most fish traders work independently without the help of other workers, with working hours averaging 61.82 hours a week and 14.23 years; 3) the income of fish traders in the traditional market of the city of Jambi is significantly affected by business capital, length of business and working hours